The Role of Placental Homeobox Genes in Human Fetal Growth Restriction - Padma Murthi; Gayathri Rajaraman; Shaun Patrick Brennecke; Bill Kalionis (Journal of Pregnancy)
Fetal growth restriction (FGR) is an adverse pregnancy outcome associated with significant perinatal and paediatric morbidity and mortality, and an increased risk of chronic disease later in adult life. One of the key causes of adverse pregnancy outcome is fetal growth restriction (FGR). While a number of maternal, fetal, and environmental factors are known causes of FGR, the majority of FGR cases remain idiopathic. These idiopathic FGR pregnancies are frequently associated with placental insufficiency, possibly as a result of placental maldevelopment. Understanding the molecular mechanisms of abnormal placental development in idiopathic FGR is, therefore, of increasing importance. Here, we review our understanding of transcriptional control of normal placental development and abnormal placental development associated with human idiopathic FGR. We also assess the potential for understanding transcriptional control as a means for revealing new molecular targets for the detection, diagnosis, and clinical management of idiopathic FGR.